Clinical treatment adherence of health care workers and students exposed to potentially infectious biological material - Maria Cristina Mendes de Almeida; Silvia Rita Marin da Silva Canini; Renata Karina Reis; Silmara Elaine Malaguti Toffano; Fernanda Maria Vieira Pereira; Elucir Gir (SciELO, 2015)
OBJECTIVE To assess adherence to clinical appointments by health care workers (HCW) and students who suffered accidents with potentially infectious biological material. METHOD A retrospective cross-sectional study that assessed clinical records of accidents involving biological material between 2005 and 2010 in a specialized unit. RESULTS A total of 461 individuals exposed to biological material were treated, of which 389 (84.4%) were HCWs and 72 (15.6%) students. Of the 461 exposed individuals, 307 (66.6%) attended a follow-up appointment. Individuals who had suffered an accident with a known source patient were 29 times more likely to show up to their scheduled follow-up appointments (OR: 29.98; CI95%: 16.09-55.83). CONCLUSION The predictor in both univariate and multivariate analyses for adherence to clinical follow-up appointment was having a known source patient with nonreactive serology for the human immunodeficiency virus and/or hepatitis B and C.